Criminal and Legal Characteristics of Theft and Fraud as Basic Personal Crimes Related to the Theft of Another Property - ZHUNUSSOV, Yeldos (Journal of Advanced Research in Law and Economics, 2019)
The article is devoted to the consideration of the criminal law characteristics of certain mercenary crimes related to the theft of another’s property, namely thefts and frauds. The relevance of the chosen subject is because theft and fraud are the most common types of theft of another's property. Thus, according to the analysis of legal statistics data, in Kazakhstan frauds take the second place among all types of crimes against property and are second only to thefts. At the same time, it was established that the types of acts prohibited by criminal law constitute more than half of the total number of pre-trial investigations. The author substantiates the position that the result of committing thefts and fraud should be causing damage directly to the owner or property owner, and not to someone else, therefore, when committing credit fraud, legal entities - banks should be recognized as the injured party. The article considers the points of view of researchers of criminal law, on the basis of which their own conclusions are formed, in particular, on determining the definition of ‘theft’, determining the age of criminal responsibility for committing qualified types of fraud, as well as on the need to introduce a qualified theft composition - committing theft from banking accounts, as well as in relation to electronic cash. Also reviewed recent changes in the legislation of Kazakhstan, which directly affected the criminal law, providing for liability for theft and fraud.